Angiotensin II receptor antagonist and ACE inhibitor effectiveness in cognitive function correction among elderly patients with arterial hypertension - S. V. Nedogoda; U. A. Brel’; T. A. Chalyabi (Кардиоваскулярная терапия и профилактика)
Aim. To assess and compare 6-month monotherapy effectiveness for losartan and lisinopril, according to their effects on blood pressure (BP), vascular elasticity, and cognitive function in patients with Stage I-II arterial hypertension (AH). Material and methods. This open clinical trial included 15 patients (10 women, 5 men; mean age 62,5±2,1 years) with Stage I-II AH who received losartan, as well as 15 individuals (11 women, 4 men; mean age 64,4±4,1 years) with Stage I-II AH who received lisinopril. Monotherapy lasted for 6 months. At baseline and 6 months later, all participants underwent 24-hout BP monitoring (BPM), echocardiography, pulse wave velocity (PWV) measurement, and neuro-psychological testing to assess cognitive function. Results. Six-month monotherapy with losartan or lisinopril resulted in significant systolic and diastolic BP reduction. Target BP levels were achieved in 40% and 37% of the participants, respectively. According to 24-hour BPM, losartan was more effective than lisinopril: after-action coefficient was 62% and 51%, respectively (p<0,05). Losartan monotherapy significantly improved cognitive function (including perception, short and long-term memory). PWV effects were similar for both medications. Losartan and lisinopril improved vascular rigidity and left ventricular hypertrophy parameters. Conclusion. Losaratan improved cognitive function more effectively than lisinopril, independently of its antihypertensive action. Therefore, losaratan should be recommended for cognitive function correction.